Falling monuments, reluctant ruins : the persistence of the past in the architecture of apartheid - Judin, Hilton (Johannesburg, South Africa : Wits University Press, 2021)
Interrogates how, in the era of decolonisation, post-apartheid South Africa reckons with its past in order to shape its future. Architects, historians, artists, social anthropologists and urban planners seek answers in this book to complex and unsettling questions around heritage, ruins and remembrance. What do we do with hollow memorials and political architectural remnants? Which should remain, which forgotten, and which dismantled? Are these vacant buildings, cemeteries, statues, and derelict grounds able to serve as inspiration in the fight against enduring racism and social neglect? Should they become exemplary as spaces for restitution and justice? The contributors examine the influence of public memory, planning and activism on such anguished places of oppression, resistance and defiance. Their focus on visible markers in the landscape to interrogate our past will make readers reconsider these spaces, looking at their landscape and history anew.
Introduction / Hilton Judin -- Part one: lands -- Land dispossession and the ghosts of the Medupi Power Station / Faeeza Ballim -- A community journey: return to Juliwe Cemetery in Roodepoort, Johannesburg / Eric Itzkin -- Public memory and transformation at Constitution Hill and Gandhi Square in Johannesburg / Temba John Dawson Middelmann -- Ejaradini: notes toward modelling black gardens as a response to the coloniality of museums / MADEYOULOOK -- Part two: buildings -- Johannesburg Central Police Station and the photograph as evidence / Sally Gaule -- The persistence of Robben Island: abolition and the prison museum / Kelly Gillespie -- The Apartheid Pass Office in Johannesburg and a heritage of destruction / Hilton Judin -- Indian trading, Art Deco and urban modernity in a segregated town: Jubliee House in Krugersdorp / Arianna Lissoni and Roshan Dadoo -- An uncertain heritage and resistance: transforming the Drill Hall in Johannesburg / Barbara Morovich and Pauline Guinard -- Part three: statues, as monuments -- Creating spaces of memorialisation: New Deville Wood (France) and SS Mendi (South Africa) / Yasmin Mayat and Brendan Hart -- Re-historicising credo Mutwa's Kwa Khaya Lendaba Cultural Village in Soweto / Ali Khangela Hlongwane and Tara Weber -- Facing (down) the coloniser? The Mandela statue at Cape Town's city hall / Cynthia Kros -- 'Where's our monument?' commemorating Indian indentured labour in South Africa / Goolam Vahed -- Decolonisation, monuments, and a new architectural language / Nnamdi Elleh.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Apartheid and architecture -- South Africa; Architecture and race -- South Africa; Architecture and state -- South Africa; Monuments -- South Africa; Historic buildings -- South Africa; Architecture et race -- Afrique du Sud; Architecture -- Politique gouvernementale -- Afrique du Sud; ARCHITECTURE -- History -- General; Apartheid and architecture; Architecture and race; Architecture and state; Historic buildings; Monuments; South Africa; Electronic book